Hiranyakarba: An Universal Golden Womb (Journal of Namibian Studies : History Politics Culture, 2023)
This article provides a detailed inscriptional data on an important ceremony or aspecial rite, “Hiranyakarba, the golden womb”, Hiranyakarbaa Sanskrit expression literally means the 'golden womb'. The golden womb a special rite conducted by the ruling classes invariably in numerous dynasties and several Kingdoms. This paper portrays the principle ceremony Hiranyakarba by Rajaraja I Chola and Rajendra I Chola and explains how the rare concept came into being what the reason behind it was.